Electrochemical synthesis of fluorescent carbon dots for the selective detection of chlortetracycline. Issue 3 (June 2022) - Lee, Yu-Sheng; Hu, Cho-Chun; Chiu, Tai-Chia
Abstract: Carbon dots (CDs) have been used for the fluorescent turn-on detection of chlortetracycline (CTC) with high selectivity and sensitivity. In this study, CDs were fabricated via electrochemical treatment using diethylenetriaminepentaacetic acid and ethylenediamine as precursors. The synthesized CDs exhibited blue fluorescence under ultraviolet irradiation and a maximum emission of 407 nm at an excitation wavelength of 325 nm; the calculated quantum yield was 2.5%. Moreover, the CDs demonstrated excellent water solubility and photobleaching resistance as well as good stability. In the presence of CTC, a considerable enhancement in fluorescence emission was observed, based on aggregation-induced emission enhancement owing to the complexation of CTC and CDs, thus providing the foundation for quantifying CTC. Under optimal conditions, the linear range was 0.8–10 μM (R 2 = 0.9944), and the corresponding limit of detection was 16.9 nM. The proposed sensing system was successfully applied for determining CTC in actual samples with good recoveries between 91.3% and 110.6%. Graphical Abstract: ga1 Highlights: Fluorescent CDs were synthesized via a facile one-pot electrochemical approach. CDs-based fluorescent probes with high selectivity were successfully fabricated. Detection of CTC was based on aggregation-induced emission enhancement. Excellent detection performance for CTC was obtained.